La gamificación en la mejora el rendimiento académico en la asignatura de lengua y literatura en estudiantes del 8° Grado. - VILLAMAR CEVALLOS, MARIA BELEN; Cevallos Jordán , Yine del Rocio; Jácome Encalada, Sofía Jácome Encalada; Rumbaut Rangel , Dayron (Revista Minerva, 2024)
The study on the effect of gamification on the academic performance of eighth grade students in language and literature involved carrying out an experiment with two groups: an experimental one, which participated in gamification activities, and a control group, which followed the traditional curriculum. To evaluate the impact, evaluation instruments were used before and after the intervention to measure the levels of academic performance in both groups. The results showed a significant improvement in the experimental group compared to the control group. This difference suggests that the incorporation of gamification in the educational process can have a positive effect on the development of language skills. Gamification provides a stimulating and engaging approach that can increase students' active participation in reading activities, offering immediate feedback and rewards that reinforce learning. By implementing gamification strategies, educators can create more dynamic and motivating learning environments, promoting engagement and collaboration among students. These results have important implications for educational practice, underscoring the need to explore and adopt innovative approaches that harness the potential of technology and gamification to improve academic outcomes in the area of ​​language and literature.